2017
DOI: 10.1016/j.homp.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of Zincum metallicum on cell models

Abstract: Differing responses and non-linearity were found on macrophages challenged with Zincum metallicum at high dilutions. No changes in melanoma cells were observed. Customised assays using target cells can be useful to investigate high-dilution effects. Other cell types and conditions should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…demonstrated that the homeopathic mother tincture of Phytolacca decandra induces apoptosis of A375 melanoma cells by activating caspases-mediated signaling and ROS generation 24 . On the other hand, no effect was observed on melanoma cells with Zincum metallicum 25 . Although these previous studies are encouraging, the particular action of the mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 87%
“…demonstrated that the homeopathic mother tincture of Phytolacca decandra induces apoptosis of A375 melanoma cells by activating caspases-mediated signaling and ROS generation 24 . On the other hand, no effect was observed on melanoma cells with Zincum metallicum 25 . Although these previous studies are encouraging, the particular action of the mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 87%
“…[45][46][47] Macrophage cultures are very sensitive for detecting the effect of high dilutions but are also sensitive for detecting such solvent changes as well, concerning elements related to cell oxidative metabolism. [48][49][50] Such biochemical interference could lead to non-specific results-that is, not related to the Similia principle itself, but to the physico-chemical changes of the solvent due to agitation. Similar solventdependent effects can also be easily seen in vegetal models.…”
Section: Discussionmentioning
confidence: 99%
“…The findings (1) and (2) above are parasite and/or macrophage features, whose mechanisms need to be elucidated in further studies, though they are probably related to the specific expression of certain genes, as already seen in other similar studies using macrophages invitro. 17,18,[48][49][50] From a practical point of view, putative overlapping between the pro-inflammatory effects of succussed water, including the induction of inflammatory cytokines and chemokines (such as MCP-1, MIP-1β and TNFα) and the specific effects of Phos 200cH (acute expression of RANTES and lysosome activation), would also be present in clinical situations. Thus, an important consideration emerges: perhaps homeopathy acts through different and simultaneous mechanisms, with diverse degrees of specificity, which could be in accordance with the systemic effects observed in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Finding cost-effective treatments for selected diseases has been a priority in our research group. Over the past years, we have investigated, in vitro (24)(25)(26)(27)(28)(29)(30)(31) and in vivo (32)(33)(34)(35)(36), the effects of highly diluted natural complexes (HDNCs). Lately, we have focused on two specific HDNCs, namely M1 and M8.…”
Section: In Vitro Attenuation Of Classic Metastatic Melanoma-related mentioning
confidence: 99%